Isoinertial technology for rehabilitation and prevention of muscle injuries of soccer players: literature review (2016)
Introduction: Soccer is the sport with the highest risk of muscle injury for players. Eccentric exercise is fundamental for reducing injury rates and isoinertial technology devices cause an increase in eccentric demands after a concentric contraction.Objective: To identify the use of isoinertial technology in the fields of physical activity and sports for rehabilitation and prevention of muscle injuries reported in scientific literature.Materials and methods: A search of scientific papers in PubMed, Google Scholar, EMBASE and Science Direct data base was performed by using the following MeSH medical terms and search equations: [isoinertial AND technology AND flywheels] and [free weight AND sport AND humans AND soccer].Results: 23 references, classified into three approaches, were selected: isoinertial technology for rehabilitation, fitness and injury prevention. The use of this technology is fundamental due to the increase of the eccentric demand in muscle groups.Conclusions: Isoinertial technology is a useful tool for treating and preventing injuries, as well as for the development of physical qualities. However, it is necessary to work on protocols that allow unifying its usage parameters so that it can be included in prevention programs.